2008
DOI: 10.5860/crl.69.6.546
|View full text |Cite
|
Sign up to set email alerts
|

The Interdisciplinary Influence of Library and Information Science 1996–2004: A Journal-to-Journal Citation Analysis

Abstract: Using citation data from Journal Citation Reports (JCR) 1996–2004, this research replicates Meyer and Spencer's analysis of other-field citations to Library and Information Science (LIS) journals from 1972 to 1994. After 1994, JCR added LIS journals emphasizing empirical, information science research and simultaneously dropped journals addressing the profession of librarianship. The newly added journals attract a broader interdisciplinary readership—a readership reflected in a 14 percent increase in other-fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…Together, these criteria ensure that the journals included in the study meet both objective and subjective standards of impact and reputation. The last two criteria also address a common complaint—that the JCR Information Science & Library Science category includes some journals that are not central to the discipline of LIS (Abrizah, Zainab, Kiran, & Raj, ; Manzari, ; Ni, Sugimoto, & Cronin, ; Odell & Gabbard, ). Thirty‐one journals met all four criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Together, these criteria ensure that the journals included in the study meet both objective and subjective standards of impact and reputation. The last two criteria also address a common complaint—that the JCR Information Science & Library Science category includes some journals that are not central to the discipline of LIS (Abrizah, Zainab, Kiran, & Raj, ; Manzari, ; Ni, Sugimoto, & Cronin, ; Odell & Gabbard, ). Thirty‐one journals met all four criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Journals and other artifacts are also used as proxies for disciplines in an effort to explore interdisciplinary connections. Import/export studies of LIS journal articles have identified five main disciplines with which the field is trading intellectually: Computer Science, Business/Management, Health/Medical Sciences, Engineering, and Communication (e.g., Erfanmanesh et al., ; Odell & Gabbard, ; Cronin & Meho, ; Huang & Chang, ; Chang & Huang, ). Analyses of theses have revealed similar disciplinary associations with Business/Management, Computer Science, Education, Communication/Journalism, and Psychology (Prebor, ; Sugimoto et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Library and information science emerged as information science was incorporated into the field of library science and library science reacted to the impact of information technology. Therefore, some of the past research focusing on LIS interdisciplinarity selected journals in only library science or information science and found that (a) LIS researchers often cite publications across disciplines (Al‐Sabbagh, 1987; Bracken & Tucker, 1989; Buttlar, 1999; Chen & Liang, 2004; Cheng, 1995; Chikate & Patil, 2008; Chung, 1995; Gatten, 1991; LaBoire & Halperin, 1976; Pluzhenskaya, 2008; Shi, 2002; Tsay, 2008), (b) LIS publications are cited by researchers from various disciplines (Goodall, Julien, Lajoie‐Paquette, & McKechnie, 2005; Meyer & Spencer, 1996; Odell & Gabbard, 2008; Tang, 2004), and (c) that LIS researchers collaborate with researchers from different disciplines (Chen & Liang, 2004; Qiu, 1992). However, most studies have used only direct citation analysis and focused exclusively on the journals cited.…”
Section: Introductionmentioning
confidence: 99%